Expository Text Writing Skills Using Google Form Media Based on the Learning Community Program at SMA Negeri 1 Teluk Bintan - Sabarullah, Iman; Abdulhajar, Encik; Zaitun; Irawan, Dody; Kumalasari, Teti; Nevrita (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study aims to explore: 1) the learning outcomes of expository text reading skills using Google Form media based on the learning community program; 2) the similarity of learning outcomes of expository text reading skills using Google Form media based on the learning community program per sample group.The population of this study were grade XI students of SMA Negeri 1 Teluk Bintan who participated in expository text reading skills learning using Google Form media based on the learning community program. They numbered 105 students divided into three parallel classes with the same number of students. The sample was determined at 84 students based on a statistical formula drawn randomly from the population group. Data on expository text reading skills learning outcomes were collected using a valid test instrument. Data were analyzed using parametric inferential statistics. The results of the study: 1) the learning outcomes of expository text reading skills using Google Form media based on the learning community program reached a mean of 81.11 exceeding the KKM of 80.00; 2) There is no difference in learning outcomes for expository text reading skills using Google Form media based on the learning community program per sample group.